Sebaran Sampah Pantai di Pulau Timor, Nusa Tenggara Timur: Kajian pada Pantai Rekreasi - Lumban Nauli Lumban Toruan; Ismawan Tallo; Suprabadevi Ayumayasari Saraswati (Department of Urban and Regional Planning, Diponegoro University, 2021)
Beach debris is an increasingly important issue to study considering its negative impact on the terrestrial and marine environment. This research aims to examine the distribution of beach debris in Timor Island as a basis for managing and overcoming waste pollution. The research was conducted in August 2020 on six government-managed tourism beaches consisting of one city (Kupang) and five regencies (Malaka, Timor Tengah Selatan, Kupang, Timor Tengah Utara, and Belu). At each location, a transect of 100 meters was made parallel to the shoreline with a transect width of 10 m perpendicular to the shoreline measured from the back of the beach. All trash in the transect was taken, then cleaned from the sand, then put in plastic bags that have been labeled. The wet litter was sun-dried before being counted. All waste was then sorted, then counted in the amount of item, weight, and length. The results showed that the entire beach had been exposed to unmanaged waste. Plastic waste dominates the entire site with a composition of numbers of items between 63 - 95% (average 80 ± 12%) and length between 60 - 93% (average 75 ± 13%). The composition of the weight of plastic waste is between 20 - 72% (average 45 ± 21%), where the weight of plastic waste does not dominate at Motadikin Beach. The dynamics of ocean currents in the eastern monsoon are thought to have played a role in causing lower debris quantification at the Motadikin Beach (Malaka Regency) and Oetune Beach (Timor Tengah Selatan Regency) than to the other four beaches located in the north of Timor Island. The source of beach debris comes from recreational activities, fishing and anchoring activities, and anthropogenic waste carried away from the sea.